PENGARUH PEMBERIAN JENIS PUPUK TERHADAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS TANAMAN SEMANGKA (Citrullus vulgaris Schard) - Kalasari, Rastuti; Syafrullah, Syafrullah; Astuti, Dessy Tri; Herawati, Novi (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2020)
Effect of fertilizer application on growth and production of several varieties of watermelon (Citrullus vulgaris, schard). This study aims to determine the response of growth and production of watermelon (Citrullus vulgaris, Schard) to various types of fertilizers and different varieties. This research has been carried out on farmers' land in Pulau Semambu Village, North Indralaya District from August to November 2019. The method used is a field experiment method with a factorial RAK layout consisting of 9 treatment combinations repeated 3 times. Factor I is the type of fertilizer (J) which consists of J1 = Baranik Fertilizer, J2 = NPK Fertilizer, J3 = Chicken Manure. Factor II is variety (V) consisting of V1 = New Dragon, V2 = Golden Crown, V3 = Possa F1. The results showed that the type of fertilizer treatment and its interactions had no significant effect on all observed variables. Varieties treatment had a significant effect on fruit weight per plant and per plot. but had no significant effect on the variables of plant height and number of leaves. The interaction treatment between NPK fertilizer and the New Dragon variety gave the highest growth and production for watermelon plants at 51.93 kg/plot.